Mass Spectral Studies on Cyclic Organophosphorus Compounds - Sikder, N.; Sikder, A.K. (Asian Journal of Chemistry, 2010)
The mass spectral studies on several structurally related series of eight, nine and ten membered cyclic phosphates with and without α-nucleophile have been studied. The fragmentation mode of cyclic phosphates under electron impact is of similar pattern and is governed by both ring size and the substituent present, thus offering a means of characterization of phosphate esters.